UV fluorescence as a method of high throughput surface cleanliness assessment: A comparison with XPS. (January 2021) - King, M.O.; Staff, M.T.; White, A.L.; Kopec, M.; Stapleton, M.; Hinder, S.J.; Watts, J.F.
Abstract: UV visible fluorescence (UV–vis) was trialled as a method for the rapid screening of surface cleanliness of metals. By comparing the relative intensity of the fluorescence to the film thickness of the carbonaceous contamination, an evaluation of the effectiveness of UV–vis was made. Surface composition and the thickness of carbon contamination on stainless steel/mineral oil and copper/tallow wax samples was measured with X-ray photoelectron spectroscopy (XPS). After vapour degreasing with trichloroethylene it was found that residual tallow wax was not effectively detected by UV–vis; whereas a commercial mineral oil was readily detected by UV–vis. The reason for the lack of fluorescence is that the tallow wax is largely an unconjugated system, in that it mostly comprises saturated or monounsaturated carbon – carbon bonds, which do not fluoresce. Using imaging XPS an increase in carbon film thickness close to the edge of the sample is observed, a result of solvent residue caused by the interfacial tension that exists between the solvent and the substrate. UK Ministry of Defence © Crown Owned Copyright 2020/AWE.